Crossmodal Language Comprehension—Psycholinguistic Insights and Computational Approaches - Alaçam, Özge; Li, Xingshan; Menzel, Wolfgang; Staron, Tobias (Frontiers in Neurorobotics, 2020)
Crossmodal interaction between vision and language is important for effective and efficient communication. The relationship between these two modalities provides mutual benefit: While vision contributes, for instance, information to improve language understanding, language in turn plays a role in driving the focus of attention in the visual environment. However, language and vision are two different representational modalities, which accommodate different aspects and granularities of conceptualizations. To integrate them into a single, coherent system solution is still a challenge, which could profit from inspiration by human crossmodal processing. Based on fundamental psycholinguistic insights into the nature of situated language comprehension, we derive a set of performance characteristics facilitating the robustness of language understanding, such as crossmodal reference resolution, attention guidance or predictive processing. Artificial systems for language comprehension should meet these characteristics in order to be able to perform in a natural and smooth manner. We discuss how empirical findings on the crossmodal support of language comprehension in humans can be applied in computational solutions for situated language comprehension and how they can help to mitigate the shortcomings of current approaches.